Determinants of Gynecological Ultrasound Utilization Among Pregnant Women: Evidence from Indonesia’s National Health Insurance Claims - Mahwati , Yeni; Hasibuan, Syarif Rahman; Nurrika, Dieta (IAKMI South Tangerang Branch, 2025)
Background: Equitable access to prenatal ultrasound (USG) is critical for improving maternal health outcomes in Indonesia. Although hospital-based USG is covered under the national health insurance scheme (JKN), utilization may vary across demographic and socioeconomic groups. Objective: To examine how maternal age, place of residence, geographic region, and insurance membership segment are associated with hospital-based USG use among pregnant women covered by JKN. Methods: This cross-sectional study analyzed the 2023 maternal health dataset from BPJS Kesehatan (Healthcare). Of 468,922 pregnant women, 13,787 with at least one hospital-based ultrasound visit (INA-CBG code Z-3-25-0) were included. Descriptive statistics and negative binomial regression assessed associations with age, domicile, region, insurance segment, and ward class. Results: Among 13,787 women with hospital-based ultrasound visits, the average utilization was two scans per year. In Model 1, regency residents had lower utilization than city residents (IRR = 0.90, 95% CI: −0.11 to −0.10), while women in Java–Bali showed slightly higher use (IRR = 1.06, 95% CI: 0.04–0.07). Utilization was lower in Sumatra (IRR = 0.89), Sulawesi (IRR = 0.84), and Kalimantan (IRR = 0.97). Compared with formal workers, lower rates were observed among subsidized groups such as PBI-APBN (IRR = 0.89), PBI-APBD (IRR = 0.90), and non-workers (IRR = 0.84). Age was positively associated with higher use (IRR = 1.01 per year). In Model 2, interaction terms revealed regional variations: for instance, disparities by insurance segment were most pronounced in Java, Sulawesi, and Kalimantan, with IRRs ranging from 0.60 to 1.09. Overall, while statistically significant, the effect sizes remained modest. Conclusion: Although in-hospital USG services under JKN are guided by clinical indications, geographic and insurance-related disparities persist. These patterns suggest the influence of structural and access-related factors, highlighting the need to strengthen equitable referral and service delivery across regions.